2019
DOI: 10.1093/mnras/stz2217
|View full text |Cite
|
Sign up to set email alerts
|

The tilt of the local velocity ellipsoid as seen by Gaia

Abstract: The Gaia Radial Velocity Spectrometer (RVS) provides a sample of 7 224 631 stars with full six-dimensional phase space information. Bayesian distances of these stars are available from the catalogue of Schönrich et al. (2019). We exploit this to map out the behaviour of the velocity ellipsoid within 5 kpc of the Sun. We find that the tilt of the disc-dominated RVS sample is accurately described by the relation α = (0.952 ± 0.007) arctan(|z|/R), where (R, z) are cylindrical polar coordinates. This corresponds t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 51 publications
8
27
1
Order By: Relevance
“…As a dynamical model, we use the JAM sph approach 7 (Cappellari 2020), which is based on the solution of the axisymmetric Jeans equations and assumes a spherically aligned velocity ellipsoid (Bacon et al 1983;Bacon 1985). The spherical alignment has proven to describe the Gaia data in the outer halo (Wegg et al 2019) and in the disk region (Hagen et al 2019;Everall et al 2019). This was also confirmed by the results in Paper I.…”
Section: Modelingsupporting
confidence: 79%
See 1 more Smart Citation
“…As a dynamical model, we use the JAM sph approach 7 (Cappellari 2020), which is based on the solution of the axisymmetric Jeans equations and assumes a spherically aligned velocity ellipsoid (Bacon et al 1983;Bacon 1985). The spherical alignment has proven to describe the Gaia data in the outer halo (Wegg et al 2019) and in the disk region (Hagen et al 2019;Everall et al 2019). This was also confirmed by the results in Paper I.…”
Section: Modelingsupporting
confidence: 79%
“…Previously, we used the Gaia Data Release 2 (DR2) kinematics to construct an axisymmetric dynamical model of the Milky Way disk (Nitschai et al 2020, hereafter Paper I). There we used the new spherically aligned Jeans anisotropic modeling (JAM sph ; Cappellari 2020) method, since the Gaia data (Everall et al 2019;Hagen et al 2019) showed that the velocity ellipsoid is closer to being spherically aligned than cylindrically (JAM cyl ;Cappellari 2008). But we also compared the results against JAM cyl and found negligible differences.…”
Section: Introductionmentioning
confidence: 99%
“…As an extreme test of the sensitivity of our model to the assumptions on the orientation of the velocity ellipsoid, we also have fit a model (JAM cyl ) which assumes a cylindrically-aligned velocity ellipsoid (Cappellari 2008). The JAM sph model gives a slightly better fit the data than JAM sph , consistently with the finding that the Milky Way velocity ellipsoid is nearly spherical aligned (Hagen et al 2019;Everall et al 2019). However, the difference between the parameters inferred by two JAM sph and JAM cyl models is minimal as the two solutions are not very different in the disc plane.…”
Section: Jam Fit To the Gaia Datasupporting
confidence: 52%
“…For the dynamical modelling we use a new solution of the axisymmetric Jeans equations under the assumption of a spherically-aligned velocity ellipsoid (Cappellari 2019), which was shown to describing very accurately the dynamics of the Gaia data both in the outer halo (Wegg et al 2019) and the disc region (Hagen et al 2019;Everall et al 2019). This JAM sph method was developed specifically with the Gaia data in mind.…”
Section: Bayesian Jam Modellingmentioning
confidence: 99%
“…On the other hand, the off-diagonal terms σ zr , σ zφ , and σ φr determine the inclination of the velocity ellipsoid which is crucial to determine the distribution of baryonic and dark matter in the Galaxy. In particular, the inclination of the SVE in the ZR plane, known as the tilt angle, is important to properly determine the dark matter distribution in the galactic plane (Büdenbender, van de Ven & Watkins 2015;Everall et al 2019;Hagen et al 2019). Furthermore, the inclination on the radial and azimuthal plane, so-called vertex deviation, in the inner regions of our galaxy allows to study the presence of non-axisymmetries such as triaxial bulges or bars (Zhao, Spergel & Rich 1994;Soto, Rich & Kuijken 2007;Simion et al 2021).…”
Section: Introductionmentioning
confidence: 99%